MicroRNA‐mediated inflammation and coagulation effects in rats exposed to an inhaled analog of sulfur mustard. Issue 1 (29th June 2020) - Rana, Tapasi; Ahmad, Aamir; Zafar, Iram; Mariappan, Nithya; Chandrashekar, Darshan Shimoga; Hamid, Tariq; Husain, Maroof; Varambally, Sooryanarayana; Ahmad, Shama; Ahmad, Aftab
Abstract: Exposure of rats to 2‐chloroethyl ethyl sulfide (CEES), an analog of sulfur mustard, can cause acute lung injury (ALI), resulting in increased inflammation and coagulation and altered levels of plasma microRNAs (miRNAs). Rats were exposed to aerosolized CEES and euthanized 12 h later for collection of tissue and plasma. Profiling of miRNAs in plasma, using a TaqMan‐based RT‐PCR array, revealed 14 differentially expressed miRNAs. Target gene prediction and pathway analysis revealed miRNA‐mediated regulation of organismal injury, inflammation, and respiratory diseases. miR‐140‐5p, a marker of ALI, was downregulated in the plasma, lung, liver, and kidney of CEES‐exposed rats, with a concomitant increase in the expression of the inflammation markers IL‐6 and IL‐1α and the coagulation marker tissue factor (F3). Exposure of rat airway epithelial cells (RL‐65) to CEES (0.5 mM) caused cell death and a decrease in miR‐140‐5p both in cells and media supernatant. This was accompanied by an increase in cellular mRNA levels of IL‐6, IL‐1α, and F3, as well as FGF9 and EGR2, putative targets of miR‐140. Knockdown of miR‐140 by specific oligos in RL‐65 cells mimicked the in vivo CEES‐mediated effects, leading to significantly increased mRNA levels of IL‐6, IL‐1α, F3, FGF9, and EGR2. Our study identifies miR‐140‐5p as a mediator of CEES‐induced ALI, which could potentially be targeted for therapy. Abstract : To evaluate the role of microRNAs in pulmonary injury caused potentially by sulfur mustard (SM), we focused on altered microRNA expression and the deregulation of inflammation and coagulation pathways in rats exposed to CEES, a sulfur mustard analog, as these pathways are well‐characterized clinical manifestations of exposure to CEES or SM. This study also investigates the functional roles of the identified microRNAs in regulating CEES‐induced toxicity.